2021
DOI: 10.21512/humaniora.v12i1.6708
|View full text |Cite
|
Sign up to set email alerts
|

Preservation of Javanese Language on Ganjar Pranowo's Conversation in Pandemic of COVID-19

Abstract: The research aimed to see a relevance of the preservation of the Javanese language in Javanese conversations that Ganjar Pranowo carried out during the COVID-19 pandemic. The resulting data was about the level in the language that included word level, phrase level, and sentence level. Also, several manners, unggah ungguh, and ethics were produced that could become examples or role models for the people of Central Java. The research applied a qualitative method. The data source was the utterances contained in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…(Ajie & Adji, 2019) Based on the answers in the interview, the script for the film Nyumbang is initially written in Indonesian, then assisted by the Sanggar Merbabu Budaya team to compose it into a regional Javanese language which is thick with the accent of the Kethoprak art. Widianto (2018) in Farichah, Rakhmawati, and Wardani (2021) have also revealed that regional languages are valuable to a nation. People in Central Java use Javanese every day.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…(Ajie & Adji, 2019) Based on the answers in the interview, the script for the film Nyumbang is initially written in Indonesian, then assisted by the Sanggar Merbabu Budaya team to compose it into a regional Javanese language which is thick with the accent of the Kethoprak art. Widianto (2018) in Farichah, Rakhmawati, and Wardani (2021) have also revealed that regional languages are valuable to a nation. People in Central Java use Javanese every day.…”
Section: Resultsmentioning
confidence: 99%
“…Following the characteristics of the Javanese people, in learning the language, one should not ignore linguistic customs, especially Javanese culture, which upholds politeness. Also, to revive national identity is especially by uploading the Javanese language into oral and written works (Farichah, Rakhmawati, & Wardani, 2021).…”
Section: Resultsmentioning
confidence: 99%